2022
DOI: 10.1029/2022ja030711
|View full text |Cite
|
Sign up to set email alerts
|

Global Structure and Seasonal Variations of the Tidal Amplitude in Sporadic‐E Layer

Abstract: Sporadic-E (Es) layer is an enhanced ionization patch composed of metallic ions (Fe + , Mg + , Na + , and Ca + ) derived from meteor deposition and ablation that appears in the mesosphere and the lower thermosphere (MLT) region. Observation and simulation results have demonstrated that Es layer formation over the middle and low latitude regions is attributed to neutral wind shear theory, in which the zonal and meridional winds provide vertical wind shear nulls where the long-lived metallic ions converge and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The diurnal variation prevails at lower latitudes, while the semidiurnal variation takes precedence at mid-latitudes. These findings align with prior research, attributing these patterns to the influence of tides on neutral horizontal winds [7,12,15,37].…”
Section: The Descending Rates Of Es Layers and Ivnsupporting
confidence: 89%
See 1 more Smart Citation
“…The diurnal variation prevails at lower latitudes, while the semidiurnal variation takes precedence at mid-latitudes. These findings align with prior research, attributing these patterns to the influence of tides on neutral horizontal winds [7,12,15,37].…”
Section: The Descending Rates Of Es Layers and Ivnsupporting
confidence: 89%
“…At the same time, the descent rate of Es layers was estimated to be between 0.9-1.6 km/h based on the occurrence rate derived from COSMIC data [12]. With the help of ionosondes and COSMIC, the signals of tide and planetary waves in the strength and height of Es were found [13][14][15] and were connected with the variations of atmospheric waves [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These 12‐ and 24‐hr periodicities have been recognized on Es formation in ionosonde measurements (Haldoupis, 2011, and more references therein). Diurnal (semidiurnal) tides are known to be stronger at low‐ (mid) latitude region compared to mid (low) latitudes and dominates the Es layers below (above) 120 km (Chu et al., 2014; Manson et al., 1999; Tang et al., 2022). From RO measurements, Chu et al.…”
Section: Results and Analysismentioning
confidence: 99%
“…Additionally, Tang et al. (2022) observed that the Es layer intensity is modulated by the semidiurnal tide from −25° to −65° and from 20° to 60° latitudes, while the diurnal tide modulates the Es layer intensity in the latitude range between ±20°. It is observed in this work that stronger power spectrum at 24‐hr compared to 12‐hr in Figure 8, except in autumn where the peak is narrowest.…”
Section: Results and Analysismentioning
confidence: 99%